Assessment of Head and Trunk Posture in Men with Cervicogenic Headache via Photogrammetry: A Pilot Study - Maedeh Bahari; Zohreh Shafizadegan; Mohammad Amani; Zahra Heidari; Abdolkarim Karimi (Vesnu Publications, 2017)
Introduction: Cervicogenic headache (CGH) is a type of chronic and recurrent headache that originates from cervical musculoskeletal impairments. The muscular disorders observed in patients with CGH, relation between head and neck posture and cervical muscles dysfunction, and association between pelvic alignment and spinal curves highlight the importance of postural assessment in these patients. Therefore, the objective of this study was the assessment of spinal and pelvic posture in men with CGH via photogrammetry in static standing position by measuring different angles. Materials and Methods: In this case-control study, 10 men with CGH and 10 healthy men with matched age and body mass index (BMI) were recruited. A digital camera was used to take photographs from anterior, posterior, and lateral views (3 photographs from each viewpoint). The postural angles were measured using the AutoCAD software. Results: Among the measured postural angles, the mean of cervical inclination (C2-T2) (P = 0.022), head horizontal alignment (P = 0.001), scapula horizontal alignment (P < 0.001), anterior superior iliac spine horizontal alignment (P = 0.031), and posterior superior iliac spine horizontal alignment angles (P = 0.038) were significantly different between the two groups. The intra-rater reliability of the different angles was high and acceptable [Intraclass correlation coefficient (ICC) > 0.72]. Conclusion: It seems that the upper cervical position of men with CGH differs from that of healthy subjects and C2 is more forward relative to the cervicothoracic spine. Therefore, the cervical inclination angle could be a suitable indicator of C2 position through photogrammetry.